Juridical Analysis of the Issuance of Sailing Approval Letters at the Municipal Office and Port Authority to Obtain Legal Certainty : Research Study on the Batam Special Port Authority and The Municipal Office - Ismet Sihombing; Erniyanti Erniyanti; Ramlan Ramlan; Soerya Respationo (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
The issuance of a Sailing Approval Letter (SPB) by the Office of Municipal Affairs and Port Authority (KSOP) is a crucial process that ensures that ships operating in Indonesian waters meet safety and seaworthiness requirements in accordance with applicable maritime regulations. This study was conducted against the background of the importance of SPB in providing legal certainty for all parties involved in shipping, as well as various obstacles faced in the issuance process at the Batam Special KSOP. This study aims to analyze juridically the procedure for issuing SPB in the Batam Special KSOP in order to obtain legal certainty, identify existing obstacles, and offer relevant solutions. The research methods used are normative juridical and empirical sociology. The normative juridical approach is carried out by analyzing related laws and regulations, such as Law Number 17 of 2008 concerning Shipping, Government Regulation Number 51 of 2002 concerning Shipping, and Regulation of the Minister of Transportation Number 39 of 2017 concerning Registration and Nationality of Ships. An empirical sociological approach is carried out through direct observation and interviews with KSOP officers, ship operators, and other related parties to get a practical picture of the implementation of SPB issuance in the field. The results of the study show that although the procedure for issuing SPB at the Batam Special KSOP is in accordance with applicable regulations, there are various obstacles such as limited human resources and equipment, ineffective coordination between agencies, and non-compliance of ship operators with regulations. To overcome these obstacles, efforts are needed to increase resource capacity, invest in technology, and improve coordination between agencies. Suggestions given include: (1) Batam Special KSOP needs to increase the number and skills of officers through training and recruitment, (2) The government should provide a budget for investment in modern equipment and technology, and (3) the community, especially ship operators, should increase compliance with regulations through participation in socialization and education programs. Thus, it is hoped that the SPB issuance process can run more effectively and efficiently, providing better legal certainty for all parties involved.